George C. Marshall servant of the American nation - Brower, Charles F. (World of the Roosevelts, 2011)
As historian and biographer Mark Stoler has observed, the extraordinary career of George C. Marshall in the first half of the twentieth century paralleled the emergence of the United States as a great power. Indeed, this great servant-leader contributed substantively to virtually every important event and issue comprising that ascendance. Bringing together a who's who of Marshall scholars, this volume examines the major roles assumed by Marshall over his five-decade career--soldier, statesman, and peacemaker; and leader and manager--to illuminate key issues and themes surrounding the man and his era.